Two new pioneer communities of Sorbus aucuparia and Sorbus aria in the southern Julian alps - Dakskobler, Igor (Hacquetia, 2016)
In the southern Julian Alps we described two communities whose tree layer is dominated by species from the genus Sorbus and noted two successional stages in the overgrowing of abandoned agricultural land (pastures, hay meadows). In the secondary succession on former subalpine pastures above the alp Planina Razor und under the Breginjski Stol ridge, where potential natural vegetation consists of subalpine beech forest, dwarf pine has been overgrown with mountain ash (Sorbus aucuparia) whose stands are classified into the new association Rhododendro hirsuti-Sorbetum aucupariae. Whitebeam (Sorbus aria) has established itself on steep former hay meadows in the belt of altimontane beech forests under Mts. Jalovnik and Krikov Vrh, on gullied slopes on mixed geological bedrock dominated by chert, and these stands are classified into the association Calamagrostio arundinaceae-Sorbetum ariae. While occupying only small areas these two pioneer stages, as the sites of some rare or protected species, are nevertheless important biotopes and play a vital role in protection against avalanches.